Обрізані празькі гроші в монетному обігу України - Козубовський, Г. (Спеціальні історичні дисципліни: питання теорії та методики, 2009)
На территории Галицкой Руси известно 16 находок пражских грошей первой половины XIV ст. Значительную часть составляют обрезанные пражские гроши Вацлава II (1300–1305), Яна Люксембургского (1310–1346) и Карла I (1346–1378). Анализ монетных находок показывает, что их большинство может датироваться 1335–1350 гг. Метрологические данные свидетельствуют, что вес обрезанных пражских грошей (1,2–2,75 г) соотносится с весом денежных единиц польских земель. Три обрезанных пражских гроша Яна Люксембургского и Карла I были в составе Борщевского клада (Киевская обл.), датированном 1380-ми гг. Четвертинка (1/4 часть монеты) весом 0,69 г может быть обрезана под вес монет первых литовских или русских монет. Sixteen finds of Prague Groschen of the first half of XIV century are known on the territory of Galician Rus. The bulk of them is represented by the clipped Prague Groschen of Wenceslaus II (1300-1305), John of Luxembourg (1310-1346) and Karl I (1346-1378) and could be dated by 1335-1350. According to the metrological data, the weight of the clipped Prague Groschen (1,2-2,75 g) is equal to the weight of Polish monetary units. Three clipped Prague Groschen (John of Luxembourg and Karl I) were found in the Borshchevsky hoard (Kyiv oblast) dated to the 1380-s. A quarter by weight of 0.69 g might have been clipped to the weight of the first Russian or Lithuanian coins.